Unveiling the Phenomenology of Professional and Domestic Stressors for Private School Teachers of Lahore, Pakistan - Puri, Ayesha Mubeen; Aziz, Fakhara; Shabbir, Aqsa; Iqbal, Naveed; Muazzam, Amina (Pakistan Journal of Humanities and Social Sciences, 2024)
The present research is a qualitative exploration of teacher stress faced by private school teachers in Lahore, Pakistan. We identified the professional and domestic stressors of teachers working in private schools in Lahore, Pakistan using thematic analysis. Digging into the forms of stress, three focus group interviews were conducted on three different school premises. Each focus group has eight participants, private school teachers having age ranges between 25 and 45 years, with inclusion criteria of being married and having at least three years of teaching experience in private sector. Professional and domestic themes such as workload, psychological challenges, consequences, and familial and personal factors were generated. Results confirmed some themes in previous research, such as administrative tasks, Coping strategies, classroom management, parenting issues, physical health, and emotional well-being. However, this research holds an exclusive aspect in exploring new themes such as meeting unrealistic deadlines, emotional labor, uncomfortable workstations, and unsupportive families. Implications were discussed.